Pengaruh Penambahan Sari Buah Tomat (Solanum lycopersicum ) Sebagai Pengencer Alami Terhadap Kualitas Penyimpanan Spermatozoa Sapi Bali (Bos sondaicus) - Astuti, Mindy Eka (Fakultas MIPA UNM, 2017)
Abstract. The purpose of this research was examine the effect of juice tomato (Solanum lycopersicum) as diluent on the quality of spermatozoa Bali cattle (Bos sondaicus). This research used Completely Random Design consisting of five treatments and three repetition. The treatmens are andromed, jus tomatoes- yolk egg – honey with concentration of 0 %, 10 %, 20 % and 30 %. The parameters were time of formation in a macroscopic (volume, color, pH and consistency) and microscopic (motility, life sperm percentage and abnormality). Observations were made at 0, 2, 4, 6 until 8 hour after refrigeration. The results showed that addition jus tomatoes (Solanum lycopersicum) was quality spermatozoa Bali cattle after refrigeration. Juice tomato- yolk egg – honey diluents with concentration of 20 % can produce of spermatozoa quality whether. Keywords: Spermatozoa, andromed, juice tomato, honey, yolk egg.